Goblet cell carcinoid of appendix: A rare case with literature review - Mitra, Bhaskar (Elsevier, 2013)
INTRODUCTION: The goblet cell carcinoid, a rare tumor of the appendix, is a separate entity from adenocarcinoma and carcinoid tumors. PRESENTATION OF CASE: We report a case of goblet cell carcinoid in our institute who presented with acute abdominal symptoms simulating acute appendicitis. DISCUSSION: Goblet cell carcinoid is a rare neoplasm with distinct histological and clinical features. The diagnosis is essentially made on histological grounds. Still the exact biological behavior of this tumor is uncertain. CONCLUSION: Considering the difficulty of clinical suspicion of this tumor, presenting as appendicitis and incidentally found during appendectomies, we review the goblet cell carcinoid of the appendix using an illustrative case report.